2006
DOI: 10.5194/acp-6-1201-2006
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic evidence for NAT, STS, and ice in MIPAS infrared limb emission measurements of polar stratospheric clouds

Abstract: Abstract.We have analyzed mid-infrared limb-emission measurements of polar stratospheric clouds (PSCs) by the Michelson Interferometer for Passive Atmospheric Sounding (MIPAS) during the Antarctic winter 2003 with respect to PSC composition. Coincident Lidar observations from McMurdo were used for comparison with PSC types 1a, 1b and 2. Application of new refractive index data of β-NAT have allowed to accurately simulate the prominent spectral band at 820 cm −1 observed by MIPAS at the location where the Lidar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
201
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(214 citation statements)
references
References 78 publications
11
201
2
Order By: Relevance
“…The ice PSCs are formed at synoptic-scale temperatures of up to 4-10 K above T ice . NAT particles are observed further downstream of the Antarctic Peninsula, which is consistent with the ice particles serving as condensation nuclei for NAT formation (Carslaw et al, 1998a;Höpfner et al, 2006b;Eckermann et al, 2009). Although mountain wave activity is most frequent at the Antarctic Peninsula (Hoffmann et al, 2016a), other orographic features in Antarctica can also play a role in PSC formation.…”
Section: A Survey Of Gravity-wave-induced Psc Formation Eventssupporting
confidence: 61%
See 1 more Smart Citation
“…The ice PSCs are formed at synoptic-scale temperatures of up to 4-10 K above T ice . NAT particles are observed further downstream of the Antarctic Peninsula, which is consistent with the ice particles serving as condensation nuclei for NAT formation (Carslaw et al, 1998a;Höpfner et al, 2006b;Eckermann et al, 2009). Although mountain wave activity is most frequent at the Antarctic Peninsula (Hoffmann et al, 2016a), other orographic features in Antarctica can also play a role in PSC formation.…”
Section: A Survey Of Gravity-wave-induced Psc Formation Eventssupporting
confidence: 61%
“…Case studies of mountain waves induced by the Scandinavian Mountains showed that the waves can cause localized cooling of up to 10-15 K (Carslaw et al, 1998b;Dörnbrack et al, 1999Dörnbrack et al, , 2002. The Antarctic Peninsula is another well-known hot spot for the formation of PSCs from mountain waves in the Southern Hemisphere (Wu and Jiang, 2002;Shibata et al, 2003;Höpfner et al, 2006b;Baumgaertner and McDonald, 2007;Eckermann et al, 2009;Orr et al, 2015). In the Antarctic polar stratosphere, waveinduced PSC formation is particularly important in fall or spring, whereas synoptic-scale temperatures in winter are usually well below the PSC formation threshold (Campbell and Sassen, 2008;McDonald et al, 2009;Noel and Pitts, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The resulting resolution is usually sufficient to highlight differences in the continuum-like emission of the different PSC types. Aerosol and cloud particles rarely produce narrow spectral features, and the strong spectral signature of NAT at 820 cm −1 is an exception Höpfner et al, 2006a).…”
Section: Mipas Cloud Measurementsmentioning
confidence: 99%
“…A transmission limit of 0.9 was defined to select the wavelength regions. In addition, wavelength regions used in former studies (Spang et al, , 2004(Spang et al, , 2005aHöpfner et al, 2006a, b) were taken into account. The CSDB spectra were generated with the Karlsruhe Optimized and Precise Radiative transfer Algorithm (KOPRA) model (Stiller, 2000), which takes single scattering into account (Höpfner, 2004).…”
Section: Cloud Scenario Databasementioning
confidence: 99%
See 1 more Smart Citation